In search of the soul of higher education: implications for the curriculum - Hashim, Rosnani (2015)
Higher education in Malaysia was a legacy from the British period of colonialism. As such the early universities namely the University of Malaya, University Putra, University Teknologi, University Teknologi MARA and University Science were developed based on the British university model underlined by the liberal, secular and utilitarian philosophy. Yet in Malaysia these universities are today, with the exception of the University Teknologi MARA, the premier research universities. Higher education in Malaysia today is also recognized worldwide and Malaysia is among the Top 10 nations with international student population. However, examination and analysis of the university mission, vision, curriculum reveals that they are not much different than they were in the early period of establishment. In commonality, these universities are geared towards producing the human capital and resources and with the aims to be ranked, and have not developed their own soul for their existence. Most of the newer established universities followed the trend they have set with the exception of the International Islamic University and Universiti Kebangsaan, another early university. This paper analyses the trend of higher education in Malaysia in the 21st century and argues that higher education in Malaysia must find its soul, excellence and originality before it decides to join in the bandwagon of international ranking and standards. Finally the paper analyses the implication of the issue for the university curriculum.